Essays on acquisition investments from emerging to developed markets - Ho, Hai Hong (2013)
The literature has little to say about M&A activities in emerging markets, especially when firms from these countries acquire targets in developed economies, yet this growing tendency has manifested itself clearly in the global markets for corporate control over the last two decades. Unsurprisingly, our understanding of what underpins their decisions to venture into more advanced economies or whether they are able to create or destroy value is still limited. Using recent data on the emerging markets, we find emerging-markets acquirers tend to acquire small firms with a relatively low stock of intangible assets in developed economies. This finding is in accordance with the strategic market entry hypothesis, which posits that acquirers aim to learn from more advanced markets through market entry and gradually consolidate their global competitive position in the long run. Nonetheless, no matter what their strategy really is, we find that it is unlikely to materialize in the long run, or at least in the course of three, four or five years. Expected synergies are likely to be overwhelmed by the strong nature of the value destruction of cross-border acquisitions and evident agency and hubris problems.